2018
DOI: 10.1136/heartjnl-2018-313269
|View full text |Cite
|
Sign up to set email alerts
|

Use of routinely captured echocardiographic data in the diagnosis of severe aortic stenosis

Abstract: A measure that used dimensionless index in place of AVA addressed discrepancies between quantitative echocardiographic data and the documented interpretation of severe aortic stenosis. These findings highlight the importance of understanding the limitations of clinical data as it relates to quality improvement efforts and pragmatic research design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…The results are in line with a recent report from an enormous database of >77 000 patients indicating that, on routine echocardiography, AVA had a low positive predictive value of 37.5% with respect to the final documented interpretation of AS severity 6. Furthermore, risk factors for overestimation of stenosis severity identified in the present study coincide with previously published causes for inconsistencies between AVA and mean pressure gradient.…”
supporting
confidence: 92%
“…The results are in line with a recent report from an enormous database of >77 000 patients indicating that, on routine echocardiography, AVA had a low positive predictive value of 37.5% with respect to the final documented interpretation of AS severity 6. Furthermore, risk factors for overestimation of stenosis severity identified in the present study coincide with previously published causes for inconsistencies between AVA and mean pressure gradient.…”
supporting
confidence: 92%
“…In the accompanying editorial Minners4 points out that these findings are congruent with the recent database study by Bradley and colleagues5 that also showed a low predictive valve of AVA for diagnosis of severe AS. The effects of small body size, low flow rates and measurement error all need to be taken into consideration.…”
supporting
confidence: 62%
“…In this context, the study by Steven Bradley and colleagues7 published in the current issue of Heart deserves particular attention. In a retrospective analysis of a huge database including transthoracic echo reports of 213 174 patients, they determined sensitivity, specificity, positive predictive value, negative predictive value and accuracy of measures for severe AS using the interpretation of the echocardiographic reader that eventually guided clinical care as the reference standard.…”
mentioning
confidence: 99%
“…In conclusion, Bradley et al 7 raise important concerns in their paper on the use of routine captured echocardiographic data in the diagnosis of severe AS. The most recent guideline and recommendation documents1 3 emphasise that a valve area <1.0 cm 2 calculated by standard continuity equation only suggests severe AS but requires careful further evaluation to decide whether AS is indeed severe when peak velocity and mean gradient do at the same time not reach the recommended cut-offs.…”
mentioning
confidence: 99%